(untitled) (Al-Academy, 2025)
Human history, with all its social, political, and religious transformations, has confirmed that belonging has been a human need that has accompanied man since the dawn of history. Thus, he found himself confronted with the need to belong to a group, a group, or a place. Regardless of age, race, or socioeconomic status, an individual always needs to feel like a member of a group with whom he shares common interests, and from which the group provides support. Belonging is one of the factors that determines the nature of a person’s relationship with his social environment and with his society, everywhere and at all times. Thus, belonging is a social human value that represents an integral part of the human being and drives him to achieve accomplishment and a sense of social responsibility. Belonging is thus a necessary need that the individual strives to fulfill and satisfy in order to overcome his loneliness and social isolation, as well as the spatial, temporal, or social alienation he may experience or feel. The concept of belonging in multicultural, multi-religious, and multi-ethnic countries—such as ours—has taken on a problematic character due to the multiplicity of types and forms of belonging, their complex overlap, and their interaction with various factors such as language, religion, heritage, and ideology. This confusion and this problematic concept, deeply rooted in our society as a result of the historical and political repercussions of recent decades, has placed a heavy burden on Iraqi creatives, who, in accordance with their moral responsibility, must contribute to uncovering this confusion and exercise an educational and enlightening role in favor of the national belonging that intellectuals and educators seek to consolidate and give supremacy over other sub-affiliations, whose existence has also become entrenched under political and geographical circumstances and has become a reality. This has contributed to the confusion and problematic nature of the concept of belonging and the problem of its plurality. Given the importance of the subject of belonging, especially when the “national” aspect of it is given priority over the secondary aspect, many children’s theatre writers in our country, Iraq, have addressed it through their texts according to various plots and stories. Among these writers, the name of Hussein Ali Harf stands out as an author and director in this field, who is considered "one of the most important Arab playwrights who knocked on the doors of children’s theater and entered it" (Harf, 2009, p. 87). He wrote "purposeful educational texts that, in their integrated elements, seek to rescue children’s culture from its lethargy, build a cultured, aware child, grant him some happiness, joy, and delight, and instill values ​​that may have been forgotten" (Harf, 2009, p. 87). Among the twenty texts written by Hussein Ali Harf, the poetic play "The Tale of Salwan the Artist" stands out as an important and solid literary and artistic model, containing multiple treatments of the idea of ​​belonging and strengthening the national aspect of it in a poetic style and through the hero, the young man (Salwan), with his multiple literary and artistic talents. Based on the above, the researcher decided to choose this text in particular as a deliberate sample to study the topic of representations of belonging in children’s theater texts. Based on the above, this research entitled “Representations of Belonging in the Children’s Play (The Tale of Silwan the Artist)” by Hussein Ali Harf.